INFLUENCE OF THE CHARACTERISTICS OF THE AUDITOR AND THE DEBT TO EQUITY RATIO AGAINST THE GOING CONCERN OPINION (Empirical Study of Manufactured Company Miscellaneous Sector Listed in Indonesia Stock Exchange Year 2013-2016) - Roby Adi Prasetyo, Riana R Dewi & Yuli Chomsatu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to examine and analyze the influence of the characteristics of theauditor and the debt to equity ratio against the going concern opinion on amanufactured company miscellaneous sector listed on the Indonesia stock exchangeyears 2013-2016. Characteristics of auditors are represented by the auditor switching,auditor specialization, auditor remuneration. The population in this research is thewhole industrial sector of the various manufacturing companies registered in BEI2013-2016 year. Sampling techniques in the study using the method of purposivesampling retrieved samples as much as 76 companies during four periods. Methods ofanalysis used are logistic regression analysis with application of SPSS version 17.0.The results of this study indicate that the variable debt to equity ratio significantlypositive effect against the opinion of going concern, whereas the variable auditorswitching, auditor specialization, and auditor remuneration have no effect against theopinion of going concern.Keywords: auditor characteristics; auditor switching; auditor specialization; auditorremuneration; debt to equity ratio; going concern opinion